Pyridine-Mediated B–B Bond Activation of (RO)2B–B(OR)2 for Generating Borylpyridine Anions and Pyridine-Stabilized Boryl Radicals as Useful Boryl Reagents in Organic Synthesis - Misal Castro, Luis C.; Sultan, Ibrahim; Tsurugi, Hayato; Mashima, Kazushi (Synthesis, 2021)
Significant developments have been achieved in recent years toward the utilization of (RO)2B–B(OR)2 for exploring transition-metal-free organic transformations in organic synthesis. Among the various combinations of Lewis bases with diborons developed so far, pyridine derivatives are simple, commercially available, and cheap compounds to expand the synthetic utility of diborons by generating borylpyridine anions and pyridine-stabilized boryl radicals via B–B bond cleavage. These borylpyridine species mediate a series of transformations in both a catalytic and stoichiometric manner for C–X activation (X = halogen, CO2H, NR2) and concomitant C-borylation, hydroborylation, C–C bond formation, and reduction reactions.1 Introduction2 Reaction Pathway for B–B Bond Cleavage of Diborons with Electron-Deficient Pyridines3 Pyridine-Mediated B–B Bond Activation of (RO)2B–B(OR)2 for Application in Organic Synthesis3.1 Dehalogenative C-Borylation3.2 Desulfonative C-Borylation3.3 Decarboxylative C-Borylation3.4 Deaminative C-Borylation3.5 Hydroborylation3.6 C–C Bond Formation3.7 Pyridine Functionalization3.8 Deoxygenation and N-Borylation Reactions4 Conclusions
Keywords: diboron; pyridine; B–B bond cleavage; borylation; single-electron transfer; radical reaction